The role of tumor necrosis factor-α promoter genetic variation in Takayasu arteritis susceptibility and medical treatment - Lv, Naqiang; Dang, Aimin; Zhu, Xilin; Liu, Ying; Liu, Yiwen; Zheng, Deyu; Hui, Rutai; Liu, Guozhang (Journal of rheumatology, 2011)
Tumor necrosis factor-α (TNF-α) is a multifunctional proinflammatory cytokine that influences the pathogenesis of Takayasu arteritis (TA). There is still no evidence of the relationship between TNF-α gene promoter polymorphisms and TA. We examined whether variations in the TNF-α promoter region may lead to TA susceptibility and disease progression. Five TNF-α gene promoter polymorphisms (-238G/A, -308G/A, -857C/T, -863C/A, and -1031C/T) were analyzed in 110 Chinese Han patients with TA, with a control group of 362 unrelated healthy individuals. Genotypes of TNF-α gene promoter polymorphisms were identified by direct sequencing. TNF-α plasma concentrations were determined by ELISA. Our results indicated that the frequency of the -863A allele was significantly lower in the patients with TA than in the controls (18.2% vs 25.7%; p = 0.011), but the significance was lost after Bonferroni correction (p(c) = 0.055). The frequency of -863CA/AA genotypes was significantly lower in the patients with refractory TA than in those with the 863CC genotype (22.4% vs 44.2%; p(c) < 0.01). The frequency of the GGCCT haplotype was significantly higher in patients than in the controls, while the frequencies of GGCAT and GGCCC haplotypes were significantly lower in patients than in controls. The plasma TNF-α concentrations were significantly lower in the subjects carrying the -863A allele than in those without. Patients with active TA had a significant increase in plasma levels of TNF-α compared with remission patients and the control group. Polymorphisms of the TNF-α promoter are not associated with TA in the Chinese Han population. The A allele of the -863C/A polymorphism is associated with decreased TNF-α expression, which might affect medical treatment.